2003
DOI: 10.1007/s00223-002-2015-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Zoledronic Acid Treatment Increases Bone Structure and Mechanical Strength of Long Bones of Ovariectomized Adult Rats

Abstract: Zoledronic acid (ZOL) is a highly potent heterocyclic bisphosphonate which has been shown to inhibit bone resorption in short-term experiments in young growing animals. In this investigation we have evaluated the effects of a 1-year administration to mature, ovariectomized (OVX) rats as a model for postmenopausal osteoporosis in order to elucidate (1) the temporal changes in urinary biochemical markers of bone turnover and femoral bone mineral density (BMD), (2) to measure changes of static and dynamic histomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
59
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 24 publications
5
59
1
1
Order By: Relevance
“…Previously, it was shown that 1 year of weekly injections of ZOL inhibited OVX-induced changes in bone microstructure and bone strength of femora and lumbar vertebrae of rats [7][8][9]. Also, in the same rats as used in this study, a single injection of ZOL prevented deterioration of bone microstructure and strength in tibiae of OVX rats for 16 weeks and a single injection at 8 weeks after OVX prevented further deterioration of structure and strength [10].…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Previously, it was shown that 1 year of weekly injections of ZOL inhibited OVX-induced changes in bone microstructure and bone strength of femora and lumbar vertebrae of rats [7][8][9]. Also, in the same rats as used in this study, a single injection of ZOL prevented deterioration of bone microstructure and strength in tibiae of OVX rats for 16 weeks and a single injection at 8 weeks after OVX prevented further deterioration of structure and strength [10].…”
Section: Discussionsupporting
confidence: 60%
“…Thus, although the study did not have the power to detect a small difference of 10%, it was adequately powered to answer the primary question and to answer secondary questions if the differences were large enough to be clinically relevant (i.e., on the order of 20%). It should also be noted that in previous studies on the effects of weekly ZOL injections on mechanical properties, group sample sizes were 16-20, offering a higher power to detect differences [7,9]. Therefore, further studies with a larger sample size are needed to distinguish between the effects of early and late ZOL treatments on vertebral trabecular microarchitecture and strength.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Após o climatério, em função da alteração não apenas da distribuição de tecido adiposo, causado pela deficiência de estrógenos, mas também pelo acú-mulo periférico de gordura, ocorre alteração do perfil lipídico e aumento da massa corporal (31) . Não verificamos, neste estudo, a influência do ácido zoledrônico no aumento da massa corporal dos animais, fato também comprovado por Reid et al (16) , Hornby et al (32) , Otrock et al (33) e Gilfillan et al (34) . Conclui-se, portanto, que o aumento da massa corpórea foi causado pela retirada dos ovários (ooforectomia) e não pelas substâncias administradas.…”
Section: Discussionunclassified